Variational inequalities of strongly nonlinear elliptic operators of infinite order - Adell T. El-Dessouky (International Journal of Mathematics and Mathematical Sciences)
The present paper deals with the study of the solvability of variational inequalities for strongly nonlinear elliptic operators of infinite order with liberal growth on the coefficients.